2020
DOI: 10.1080/15487733.2020.1785095
|View full text |Cite
|
Sign up to set email alerts
|

Doing laundry in consumption corridors: wellbeing and everyday life

Abstract: In this article, we explore the possibilities for a transformation toward more sustainable energy usage by engaging with mundane activities, such as doing the laundry. Across European households, laundry practices rely on social norms and material arrangements, which makes these practices rather "sticky" and resistant to change. Through the lens of consumption corridors, and accounting for wellbeing in relation to the basic needs of participation, health, and autonomy, we study laundry practices and their tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Two distinct literatures have become especially prominent in this field: the research on socio-technical transitions (and the multi-level perspective (MLP) in particular) (e.g., Geels 2002;Schot and Geels 2008) and applications of social practice theory (SPT, e.g., Shove and Walker 2010). Moreover, there is a growing body of research that aims to identify crossovers and intersections in these two approaches (e.g., McMeekin and Southerton 2012;Shove and Walker 2010), as well as to provide empirical examples of practice-based approaches to transformative change (e.g., Godin, Laakso, and Sahakian 2020;Hargreaves, Longhurst, and Seyfang 2013;Heiskanen et al 2018;Kaljonen et al 2020;Laakso 2017;Seyfang and Gilbert-Squires 2019). The objective of this article is to contribute to these efforts, by creating further dialogue between transition and practice theories.…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct literatures have become especially prominent in this field: the research on socio-technical transitions (and the multi-level perspective (MLP) in particular) (e.g., Geels 2002;Schot and Geels 2008) and applications of social practice theory (SPT, e.g., Shove and Walker 2010). Moreover, there is a growing body of research that aims to identify crossovers and intersections in these two approaches (e.g., McMeekin and Southerton 2012;Shove and Walker 2010), as well as to provide empirical examples of practice-based approaches to transformative change (e.g., Godin, Laakso, and Sahakian 2020;Hargreaves, Longhurst, and Seyfang 2013;Heiskanen et al 2018;Kaljonen et al 2020;Laakso 2017;Seyfang and Gilbert-Squires 2019). The objective of this article is to contribute to these efforts, by creating further dialogue between transition and practice theories.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for research to be reproduced in other cultural contexts and countries and to explore what encompasses a need for individuals and communities, as well as to examine what are suitable satisfiers for those needs relevant to their context. Given that our study indicates that it is important to consider perceptions of necessity and luxury items from a comfort and convenience perspective, future researchers interested in the creation of consumption corridors may wish to consider incorporating an alternative practice theoretical perspective (see Jensen et al 2019;Sahakian et al 2019;Godin, Laakso, and Sahakian 2020), which may better enable a critical in-depth exploration of existing expectations around the notions of comfort and convenience.…”
Section: Discussionmentioning
confidence: 99%
“…This study relied on self-reported data and such data are susceptible to numerous biases such as recall bias, confidence bias, and/or social desirability bias, which may limit the interpretation and generalization of the study's findings. Although self-report measures utilized on surveys often provide a pragmatic and cost-effective way to measure pro-environmental behaviors (Fahy and Rau 2013), researchers who attempt to measure and report pro-environmental behaviors through the use of reported behavioral indices on survey instruments must be cautious of inaccurate reporting of actual behaviors (Barr and Prillwitz 2013;Gatersleben, Steg, and Vlek 2002;Viklund 2004). Another potential weakness related to scale (both in time and space) is inherent when employing this type of methodological approach.…”
Section: Methodsmentioning
confidence: 99%
“…Two other contributions consider how consumption corridors might play out in relation to specific consumption domains. In the initial instance, Godin et al (2020) explore consumption corridors through the mundane activity of doing the laundry. Across European households, laundry practices rely on social norms and material arrangements, which makes these practices rather "sticky" and resistant to change.…”
Section: Introducing the Contributions In This Special Issuementioning
confidence: 99%